MODIFIED RUBBER PARTICLES AND COMPOSITIONS INCLUDING THE SAME - SHAHIDI NIMA; ARASTOOPOUR HAMID; TEYMOUR FOUAD (2010)
Modified scrap rubber particles, a method for forming the modified rubber particles and compositions including the modified rubber particles. The rubber particles are impregnated with at least one polymerizable monomer and polymerized to impregnate the rubber particles with a polymer. The impregnated polymer provides the modified rubber particles with improved properties which increase the potential uses for recycled scrap rubber. The modified rubber particles are useful in surface coatings, such as latex paint or powder coatings and can be used as a soil substitute.